Formic acid poisoning with suicidal intent: a report of 53 cases. Issue 711 (January 1985) - Rajan, N.; Rahim, R.; Krishna Kumar, S.
Abstract : A report of 53 cases of formic acid ingestion with suicidal intention is presented. The patients were seen in one hospital in Kerala State over a 3 year period. Fifteen patients died and 38 patients survived. The pattern of clinical features seen is presented.